Rupture of a hepatic hydatid cyst towards the chest cavity after an abdominal-chest trauma. Difficulties in the diagnosis - Castañeda Saldaña, Enrique (2021)
Cystic hydatidosis is a zoonotic infection caused by the cestode Echinococcus, which is endemic in many regions of Peru. Hydatid cysts are usually located in the liver and lungs, locations elsewhere are rare as well as multiple hydatidosis. Most of the hydatid cysts are asymptomatic and are found incidentally. Rare complications may arise such as spontaneous or traumatic rupture (3-17%), it is very infrequent that the hydatid cyst rupture towards the chest wall. We present a case of a patient who suffered the rupture of hepatic cysts into the pleural cavity after an abdominal-chest trauma, the rarity of this event made the identification of the problem more difficult to be confused with massive hemothorax. Careful review of the CT-Scan images allowed to reach the correct diagnosis.